Procaterol but Not Dexamethasone Protects 16HBE Cells From H2O2-Induced Oxidative Stress - Zheng Deng; Jun-Jun Zhou; Shuang-Yong Sun; Xin Zhao; Yi Sun; Xiao-Ping Pu (Journal of Pharmacological Sciences, 2014)
Abstract.: Oxidative stress is an important pathophysiological factor of asthma and chronic obstructive pulmonary disease (COPD). We hypothesized that procaterol and dexamethasone might treat inflammation through inhibiting oxidative stress in vitro. This study evaluated procaterol and dexamethasone in the hydrogen peroxide (H2O2)-induced immortal human bronchial epithelial cell model of oxidative stress and investigated the underlying mechanisms. Results showed that exposure to 125 μM H2O2 for 2 h led to a 50% reduction in the cell viability, significantly increased the percentage of apoptosis, and elevated levels of malondialdehyde and reactive oxygen species. Pretreatment with procaterol (25 – 200 nM) could reduce these effects in a dose-dependent manner. In contrast, pretreatment with dexamethasone (100 nM, 1000 nM) was inefficient. Pretreatment with procaterol plus dexamethasone (100 nM procaterol + 1000 nM dexamethasone) was effective, but the combined effect was not more effective than the sole pretreatment with 100 nM procaterol. The nuclear factor kappa-B (NF-κB) pathway was involved in the pathogenic mechanisms of H2O2. Procaterol may indirectly inhibit H2O2-induced activation of the NF-κB pathway due to its capability of antioxidation. Glucocorticoids may be not recommended to treat asthma or COPD complicated with severe oxidative stress. Keywords:: oxidative stress, procaterol, dexamethasone, nuclear factor kappa-B, hydrogen peroxide